Experimental Study of the Morphological Evolution of a Reef Island under Regular Waves - Zhang Xinyi; Yao Yu; Chen Long; Chen Xianjin (Redai dili, 2023)
Reef islands are composed of unconsolidated carbonate sediment from the reef that has been organized and deposited on an atoll and platform reef by ocean hydrodynamics. They are frequently found in remote mid-ocean locations within tropical and subtropical waters and are the sole source for habitable land of some island nations. It is anticipated that sea level rise and more frequent and intense storms resulting from global climate change will destabilize these low-lying reef islands, thus there is increasing concern about the persistence and habitability of these islands during future extreme wave events. The reef island morphodynamic response to the action of regular waves has not been reported in the literature. Therefore, this study performed laboratory experiments based on a horizontally one-dimensional reef island physical model in a wave flume. The temporal variation of the island profile under regular waves was measured to analyze the effects of island morphological factors (initial island height and width) and initial island location on its topographic evolution. The results showed that the reef island lost crest elevation and migrated and extended toward its lagoon side under the action of regular waves. Accretion also occurred on the lagoon side beach and random ripples appeared. The time required for the island to reach its equilibrium profile decreased with increasing of initial island height, initial island width, and initial island distance from reef edge. The island crest lowering due to scouring increased with increase of initial island height, but it decreased with increasing of initial island width and initial island distance from the reef edge. Among the three factors, initial island height had the greatest impact on the crest lowering. The island lagoonward migration decreased with increasing of both initial island height and initial island distance from reef edge, but it increased with the increase of initial island width. Among the three factors, initial island location was the most influential factor to lagoonward migration, but no island lagoonward migration was detected when the initial island distance D≥2 m. Regression analysis was used to obtain empirical formulae to predict the island crest lowering and island lagoonward migration, respectively. The outcomes of this study provide a habitability assessment for such low-lying island nations in the context of global climate change.